“Bonus of Demography” as an Opportunity to Build Indonesian’s Welfare (Through the Role of Doctors in Primary Care in the STBM Program for Decreasing the Prevalence of Stunting) - Mariatul Fadilah (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2019)
Demographic bonus is a condition where the composition of the population of productive age (age range 15-65 years old) is greater than the number of non-productive age population. According to BPS predictions, in 2020-2045 Indonesia has the opportunity to experience a demographic bonus, in which the country will have around 180 million productive-aged people, while those who are not productive are 60 million. Currently, 3 to 4 unproductive people will be rewarded by 10 productive people. In 2018 the total population of Indonesia is 265 million with a composition of 133.17 million women and 131.88 million men, where the population dependency ratio of Indonesia is 47.9%, which means there are 47 to 48 unproductive residents (aged under 15 years old and over 65 years old) who will be borne by 100 productive age population (15-65 years old). The problem is not the quantity of productive population but more towards its quality, so large a number will really make a bonus for the development of the Indonesian nation or on the contrary the explosion of population in this productive age will be a disaster for this beloved nation.